Strange Loops, Vicarious Causation, and More-Than-Human Consciousness: Toward a Post-Anthropocentric Synthesis of Harman and Hofstadter - Bower, Richard (Cosmos and History: The Journal of Natural and Social Philosophy, 2025)
This essay conjectures a novel intersection of Graham Harman’s Object-Oriented Ontology (OOO) and Douglas Hofstadter’s inquiries into human cognition. Prompted by Harman’s use of metaphor and Hofstadter’s exploration of analogy, the essay explores the origins and implications of these linguistic devices as distinct depictions of ontology and consciousness: metaphor as necessitated by the ontological withdrawal of objects, and loops of analogous perception as the intrinsic foundation of cognition. This intersection affords a subsequent contestation of Hofstadter’s depiction of human consciousness and identity against Harman’s unresolved depictions of speculative polypsychism as a necessity of post-anthropocentric ontologies. Drawing on Quentin Meillassoux’s break from correlationism, Jane Bennett’s thing-power, and Ian Bogost’s alien phenomenology, we argue that Gödelian incompleteness exemplifies the irreducible withdrawal of objects. Ultimately, the implication of analogy and metaphor in both Hofstadter’s and Harman’s work is conjectured as an irresolvable limitation of anthropocentric representation, leading to the novel translation of Gödel’s ‘Incompleteness Theorem’ (via Hofstadter) as a possible realisation of the withdrawn unknowability of objects advocated in Harman’s OOO.